2023
DOI: 10.1209/0295-5075/acc4e5
|View full text |Cite
|
Sign up to set email alerts
|

Gauge symmetry of the chiral Schwinger model from an improved gauge unfixing formalism

Abstract: In this paper, the Hamiltonian structure of the bosonized chiral Schwinger model (BCSM) is analyzed. From the consistency condition of the constraints obtained from the Dirac method, we can observe that this model presents, for certain values of the α parameter, two second-class constraints, which means that this system does not possess gauge invariance. However, we know that it is possible to disclose gauge symmetries in such a system by converting the original second-class system into a first-class one. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However kinetic energy-like terms [29], and even the combination of mass-like and kinetic energy-like terms [33] are found to materialize as a counter term. A very recent study related to gauge symmetry (gauge unfixing) of chiral bosons is found in [34] and similar types of studies on non-commutative chiral boson is considered in [35]. Application of the gauge unfixing in the chiral Schwinger model is reported in [36].…”
Section: Introductionmentioning
confidence: 86%
“…However kinetic energy-like terms [29], and even the combination of mass-like and kinetic energy-like terms [33] are found to materialize as a counter term. A very recent study related to gauge symmetry (gauge unfixing) of chiral bosons is found in [34] and similar types of studies on non-commutative chiral boson is considered in [35]. Application of the gauge unfixing in the chiral Schwinger model is reported in [36].…”
Section: Introductionmentioning
confidence: 86%
“…Concerning gauge achievability, the gauge-fixing function Γ 1 must be chosen in such a way that the determinant in the integration measure in (54) does not vanish. This concludes the functional quantization of the gauge-invariant description of the NCCB, with gauge transformations generated by Ω 1 .…”
Section: Brief Review Of the Modified Gu Formalism -mentioning
confidence: 99%
“…Nonetheless, we claim that a consistent NCCB abelianization can be done without the need of any auxiliary fields whatsoever. That is one of the main advantages of the gauge-unfixing (GU) method [47][48][49][50][51][52][53][54][55]. Building on the original work of Mitra and Rajaraman [47], which first conjectured the interpretation of second-class constraints in phase space as resulting from gauge-fixing conditions within a larger gauge-invariant theory, Anishetty and Vytheeswaran constructed a Lie projection operator, whose action in the second-class functions was able to reveal hidden symmetries [48][49][50].…”
mentioning
confidence: 99%
See 2 more Smart Citations